Instructors’ perspectives in design and L-MOOCs: a qualitative look - Diordieva, Cristina (2024)
This qualitative phenomenological study investigates international instructors’ perspectives and experiences in designing a successful language-based massive open online course (L-MOOC). Detailed information was gathered during Summer 2018 about the instructor’s challenges and strategies through semi-structured interviews with seven participants in six different countries: Ireland, Italy, Norway, Spain, the United Kingdom, and the United States. The findings indicated that curating and facilitating a learning environment with a design team helps create an efficient L-MOOC delivery. Additionally, having multiple moderators per course and using forums helps with monitoring learners’ progress. Moreover, according to these seven L-MOOC instructors, having a course platform with rigid structures prevents using multiple activities and assessment tools for language learning. Interviewees argued that it is important to implement a learner-centered approach in L-MOOC, where learners can interact with each other and construct their knowledge. Future research studies may include exploring L-MOOC to address the best instructional practices and contribute to expanding research in language education in massive open online course environment.